Fungal pathogens causing postharvest anthracnose and fruit rot in Indian jujube (Ziziphus mauritiana) from northern Thailand and their fungicide response profiles - Nuangmek, Wipornpan; Suwannarach, Nakarin; Sukyai, Sahattaya; Khitka, Bunruam; Kumla, Jaturong (Frontiers in Plant Science, 2025)
Indian jujube (Ziziphus mauritiana) is an economically important crop in Thailand. During 2024–2025, anthracnose and rot symptoms were observed on postharvest Indian jujube fruits in northern Thailand. Thus, this study aimed to identify the causal agents and evaluate their fungicide response. Nine fungal strains were isolated and identified as Colletotrichum fructicola, C. siamense, and Fusarium weifangense through morphological and multi-gene phylogenetic analyses. Pathogenicity tests confirmed C. fructicola and C. siamense cause postharvest anthracnose, while F. weifangense causes fruit rot. Fungicide assays revealed that C. siamense was completely inhibited by copper oxychloride and copper hydroxide, with captan, cyproconazole, difenoconazole + azoxystrobin, and difenoconazole also showing effectiveness against most strains. Colletotrichum fructicola was most effectively inhibited by difenoconazole, although no fungicide achieved complete inhibition. Fusarium weifangense was fully inhibited by carbendazim, copper hydroxide, and cyproconazole, but was not suppressed by azoxystrobin. This represents the first report of C. fructicola and C. siamense causing anthracnose in Indian jujube in Thailand, and the first worldwide report of F. weifangense causing fruit rot in this crop. These findings provide crucial insights for developing effective management strategies against postharvest diseases of Indian jujube.